The assessment of retailing eficiency using network DEA - Vaz, Clara B. (2005)
The objective of this paper is to develop a methodology, based on Data Envelopment Analysis, to assess and improve the performance of retailing organisations with multiple units (shops). The methodology developed is applied to a case-study consisting of 78 supermarkets to ensure its relevance and applicability to real-world assessments. The Decision Making Units (DMUs) of retailing organisations are complex and often include multiple sub-units. For example, in the case of supermarkets, the shops are usually organised in sections that sell different products (e.g., grocery, perishables, textiles, light bazaar and heavy bazaar). This paper proposes assessing the retailing shops considering the DMU at the section level, whose efficiency levels can be obtained from a comparison with similar sections from other shops. This is consistent with the adoption of a commercial perspective for the assessment, such that the outputs are volume of sales, and the inputs measure the resources available at each section (area, stock and number of references available). This analysis is further refined with the inclusion of an additional input reflecting the value of products wasted in the shop floor, which often represents a significant proportion of the operational costs. This analysis enables the identification of benchmarking sections across all retailing stores under analysis.